2004
DOI: 10.1016/j.jacc.2004.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced atrial fibrillation

Abstract: Atrial fibrillation (AF) is the most common sustained rhythm disorder observed in clinical practice and predominantly associated with cardiovascular disorders such as coronary heart disease and hypertension. However, several classes of drugs may induce AF in patients without apparent heart disease or may precipitate the onset of AF in patients with preexisting heart disease. We reviewed the literature on drug-induced AF, using the PubMed/Medline and Micromedex databases and lateral references. Successively, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 78 publications
2
59
1
4
Order By: Relevance
“…Second, several classes of drugs have been reported to induce AF in patients. 21 The mechanisms considered responsible include adrenergic stimulation and cardiotoxicity.…”
mentioning
confidence: 99%
“…Second, several classes of drugs have been reported to induce AF in patients. 21 The mechanisms considered responsible include adrenergic stimulation and cardiotoxicity.…”
mentioning
confidence: 99%
“…Acute temporary causes of AF include alcohol abuse, excessive coffee intake, surgery, pericarditis, myocarditis, and pulmonary embolism. Medications also have been associated with the induction of AF both in case reports and clinical trials (5). This is one report of a first-detected, symptomatic AF probably due to cardiac toxicity of azathioprine.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, it was revealed that administration of EHE to mice causes atrial fibrillation, one type of cardiac arrhythmia. Atrial fibrillation had been reported to be induced by β 1 adrenergic receptor agonists such as dobutamine and arbutamine, 29) or hypokalemia. 30) Hypokalemia was reported to be induced by ephedrine administration, 31) so we measured serum potassium levels.…”
Section: Discussionmentioning
confidence: 99%